The Effectiveness of Jobsheet Development in Basic Electrical and Electronics Subject Class X TITL at SMK Negeri 1 Bangkinang - Sonia Sonia; Oriza Candra (JTEV (Jurnal Teknik Elektro dan Vokasional), 2021)
This study aims to produce a product in the form of an effective Basic Electrical and Electronics practicum for students of class X TITL at SMK Negeri 1 Bangkinang. This type of research is a research and development type, where this research uses a 4D development model with four stages, namely definition, design, development and dissemination. Data collection in this study was carried out using four research instruments, namely validation questionnaires, practicality questionnaires, work assessment sheets (rubrics) and distribution questionnaires. The results obtained in the limited effectiveness trial, with an average score of students who completed 90% with the number of students 9 out of 10 students who had fulfilled learning mastery according to classical mastery requirements, namely >85% with an effective category to use. Thus, the Basic Electrical and Electronics practicum worksheet is declared to have been effectively used in the DLE practicum in class X TITL at SMK Negeri 1 Bangkinang.